Human-microbes symbiosis in health and disease, on earth and beyond planetary boundaries - Doré, Joel; Ortega Ugalde, Sandra (Frontiers in Astronomy and Space Sciences, 2023)
Humans are microbial, ecosystems and symbioses. The relationship that humans have with their microbiomes is an essential element to maintaining health and well-being. Recent changes in lifestyles may have fostered an alteration of this symbiosis, which is frequently associated with chronic disorders. Here, we will review the state of the art on the central role of human-microbes symbiosis in health and disease, highlighting the innovations expected from the emerging knowledge on host-microbes symbiosis, for diagnosis, preventive nutritionnutrition, and a medicine of the 'microbial human'. Since microbiome science also impacts several sustainable development goals of the Planetary Boundaries Initiative, we will also explore how microbiome science could help to provide sustainability tools and strategies aligned with the life support systems sought by the Micro-Ecological Life Support Systems Alternative (MELiSSA) Project lead by the European Space Agency (ESA).